WACANA LOKAL DALAM PENDIDIKAN SURAU STUDI FILOLOGIS TERHADAP NASKAH MANTIQ - Yusri Akhimuddin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
The problem of this research was what and how local discourse found in the script of mantiq as instructional material in traditional informal Islamic educational institution (surau). The method employed was basic method by referring to philological steps. The findings showed that: first, the way the Arabic letters were written did not show similarity to that of one of standard Arabic fonts among the Arabic speaking people. Second, there were meanings of vocabulary below the texts written in Minangkabaunese dialect using Malay-Arabic letters. The materials for mantiq, nahwu, and balaghah were found in single script (text). As the instructional materials, such three components support the competency for fluent speaking, appropriate logic and aesthetic choice of language as applied in pasambahanKata Kunci: wacana lokal, naskah mantiq, pendidikan surau.